Blending‐type approximation by Lupaş–Durrmeyer‐type operators involving Pólya distribution. (8th April 2021) - Kajla, Arun; Mohiuddine, S. A.; Alotaibi, Abdullah
Abstract : In the present work, we construct a new sequence of positive linear operatorsinvolving Pólya distribution. We compute a Voronovskaja type and a Grüss–Voronovskaja type asymptotic formula as well as the rate of approximation by using the modulus of smoothness and for functions in a Lipschitz type space. Lastly, we provide some numerical results, which explain the validity of the theoretical results and the effectiveness of the constructed operators.